Description of the first flightless platynine ground beetle preserved in Baltic amber (Coleoptera: Carabidae) - Schmidt, Joachim; Göpel, Torben; Will, Kipling (Zootaxa, 2017)
Species of the megadiverse ground beetle tribe Platynini occur on all continents except Antarctica. It has been long recognized that platynine beetles were preserved in the Eocene Baltic amber. However, thus far only a single Eocene fossil has been described to the species level. In the present paper, a new species of Platynini known only as an amber inclusion fossil is described and imaged using light microscopy and micro X-ray computed tomography. Since this species cannot be assigned to any of the recently described genera, the monotypic genus Praeanchodemus gen. n., with the type species P. punctaticeps sp. n., is erected. There is some evidence from external morphology that Praeanchodemus gen. n. is part of a lineage comprising the recent genera Paranchodemus, Rhadine, and Tanystoma. However, since some synapomorphies were not found, the true relationships of the fossil taxon remain moot.